Creator Economy as a New Trend: Business Management Implications in the Digital Influencer Era - Muhammad Irfan Aditama (Maneggio, 2025)
The creator economy phenomenon marks a shift in the economic paradigm from material production to symbolic production oriented toward attention, creativity, and social legitimacy. This study aims to analyze the implications for business management in the context of the development of the creator economy and the role of digital influencers as key actors in this ecosystem. Using a qualitative phenomenological approach, this study explores the experiences, strategies, and dynamics of relationships between creators, brands, and digital platforms through in-depth interviews and participant observation. The results show that economic value is now built through symbolic interactions, identity performativity, and emotional collaboration between creators and audiences. Meanwhile, business management structures are transforming toward a more flexible, participatory, and social network-based collaborative model. However, dependence on platform algorithms creates new power asymmetries and ethical challenges for the sustainability of the creator economy. Therefore, business management in the digital era needs to develop strategies oriented not only toward economic efficiency but also toward digital ethics, transparency, and social sustainability. These findings confirm that the creator economy is a new form of participatory capitalism that demands the integration of technological logic, cultural values, and managerial responsibility